Differential expression of MAP3K7 and TROPONIN C proteins and related perturbations in renal amyloidosis - Gupta, Nimisha; Sahar, Tahreem; Khullar, Dinesh; Jain, S K; Wajid, Saima (Expert review of proteomics, 2020)
Renal amyloidosis (RA) is a rare protein misfolding disorder that prompts progressive renal insufficiency. This study aimed to decipher proteomic changes in human sera to understand the pathophysiology and molecular mechanisms underlying the disease development, hence assisting in the diagnosis of RA. Serum proteomic analysis was performed using a gel-based approach followed by MALDI-TOF MS. RA patients with age and sex matched healthy volunteers were recruited from Max Super Speciality Hospital, New Delhi, India. Proteome profiles of serum revealed eight differentially expressed proteins namely, Zinc finger protein 624, Protein FAM183A, Calcium-binding mitochondrial carrier protein Scamc-3, V-type proton ATPase 116 kDa subunit A isoforms 2, Protein TXNRD3NB, ATP - dependent RNA helicase, Troponin C and Mitogen-activated protein kinase kinase kinase 7. These proteins were reported first time in RA. The increased levels of MAP3K7 and TROPONIN C were validated by bio-layer interferometry and their diagnostic accuracy was evaluated by ROC curve analysis. The differentially expressed proteins were predominantly associated with vesicular trafficking, transcriptional regulation, metabolic processes, apoptotic process and mitochondrial metabolism. The results indicate that these proteomic signatures may be considered as potential molecular targets for RA diagnostics and therapeutics subject to validation on large sample size. AβP= Amyloid-beta protein, Aβ=Amyloid-beta, AL= Light chain amyloidosis, AA= Amyloid A, ALECT2= LECT2 amyloidosis, APS= Ammonium persulfate CKD= Chronic Kidney Diseases, EBRT= external beam radiation therapy, ESRD= End-Stage Kidney Disease, Glis2= Gli-similar 2, JNK= c-Jun NH 2-terminal kinase, MAPK= Mitogen-Activated Protein Kinase, MM=Multiple Myeloma, PHD= Prolyl hydroxylase, RA = Renal Amyloidosis, SAA= Serum Amyloid A, SD= Standard Deviation, Sepp= Selenoprotein, SCC= Squamous cell carcinoma, SDS= Sodium dodecyl sulfate, TEMED = tetramethyl ethylenediamine, TGF-Beta-1=Transforming growth factor- Beta-1, Trx = Thioredoxin, TrxR= Thioredoxin reductase.